The Influence of Islamic Corporate Governance on The Performance of Maqashid Sharia in Sharia Banking in Indonesia - Safitri, Ria; Mukhibad, Hasan (Universitas Negeri Semarang, 2020)
This study aims to examine the effect of Islamic Corporate Governance (ICG) that consist of Sharia Supervisory Board (SSB) which is measured using education level, ratio of independent commissioners, and board of director meetings on maqashid sharia performance. The population in this study was Islamic Bank listed on the Financial Services Authority (FSA) in 2013-2018 as many as 11 Islamic Banks. The sampling technique used in this study was purposive sampling method and obtained as many as 54 units of analysis. Data collection used documentation technique. The analytical method used in this study was panel data regressions using Eviews 9. The results of the study indicate that Sharia Supervisory Board (SSB) which is measured using education level, ratio of independent commissioners, and board of director meeting of board do not have effect on maqashid sharia performance. The conclusion of this research is that maqashid sharia performance of Indonesian Islamic Bank just 34.138 %, that means maqashid sharia has not been a target priority in Indonesian Islamic Bank. Thus, the factors examined have not been optimized yet for achieving the goal of sharia (maqashid sharia).